Thin Layer Chromatography Fingerprint Analysis of Tempuyung (Sonchus arvensis L.) - Sri Fauziah; Ade Heri Mulyati; Puput Melati; Mohamad Rafi; Eti Rohaeti (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
Thin layer chromatography (TLC) fingerprint profile analysis can be used for quality control of herbal medicinal raw materials through identification, authentication, and discrimination. This study aims to develop a fingerprint analysis method for tempuyung TLC (Sonchus arvensis L.), which is then used for quality control. Tempuyung was extracted with methanol using ultrasonication which was then analyzed using the developed fingerprint TLC method. The optimum mobile phase used to separate compounds from tempuyung was a composition of chloroform: ethyl acetate: dichloromethane: formic acid (7.5:2:0.5:0.1) and produced eleven bands. The mobile phase composition produced good separation and had a typical luteolin band with an Rf value of 0.22, detected under UV 366 nm and derivatized with 10% sulfuric acid reagent. This method was applied to tempuyung from three locations, including Malang, Solo, and Yogyakarta, whose fingerprint patterns did not differ significantly. The fingerprint method has been validated and met the acceptance requirements for quality control of tempuyung.